KETERAMPILAN MENULIS CERITA MENGGUNAKAN MEDIA KARIKATUR PADA SISWA MTsN LAMONGAN - Maktuf Maktuf (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2014)
The purpose of the study is to know the teachers and st udents activities, achievement and responses in writing story skill used caric ature media to the VIIC grade of Religion Junior High School State (MTs N) of Lamongan. The less uninterested students and strategies are the problems for students to get difficulties in writing skill. The researcher uses classroom action research design, the data analysis uses descriptive qualitative and descriptive quantitative. The minimal standard mark of this subject is 75.00. The result finding shows the average mark, 56.002, in the first cycle that is categorized less mark. The i ncreasing of writing story shows in second cycle, it proves the average mark, 75.316, it means the significant increasing 19.314or 55.182%. Writing story skill that used caricature media can improve the students’ behavior to ready study more active, enthusiastic in joining the teaching learning process.